Doris Kearns Goodwin and Thomas J. Farrell on the History of the 1960s - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In the opening and closing sections of the present essay, I succinctly highlight Dr. Doris Kearns Goodwin’s new 2024 book An Unfinished Love Story: A Personal History of the 1960s(Simon & Schuster). In the wide-ranging and somewhat lengthy middle section of the present essay, I construct my own personal history of the 1960s. I especially highlight the work of my former teacher in the 1960s, the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong(1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University.